Número óptimo de ovocitos: modelo de predicción para fertilización in vitro. - López-Rioja, M. J.; Campos-Cañas, J. A.; Recio-López, Y.; Quiroz-Garza, G.; Sánchez-González, C. M.; Hinojosa-Rodríguez, K.; Laresgoiti-Servitje, E. (Ginecología y Obstetricia de México, 2017)
OBJECTIVE: Develop a model to optimize the reproductive outcome (live birth rate). Identify the minimal number of oocytes to capture. MAERIALS AND METHODS: Observational, longitudinal, and retrolective study was made. In fresh IVF cycles, performed at INPer between 2011-2016. A logistic regression model was fitted with a CHAID, and performed a decision tree to predict live birth (LBR). Inclusion criteria: patients over 18 years of age, diagnosed with infertility, who underwent in vitro fertilization with fresh embryo transfer (FIV-TE). The study variables were: age, BMI, basal FSH concentration, type of infertility, time of infertility and number of oocytes captured. A decision tree type CHAID and a binary logistic regression model were performed. Statistical Package for Social Sciences (SPSS) was used for the statistical analysis. The probability of error alpha <5% was considered significant. RESULTS: A total of 673 cycles were studied. The optimal number was >12 oocytes (OR = 4.666, 95% CI: 2.676-8.137, p=<0.01). The highest chance to have LB (28%), was in women <37 years old, with FSH <4.2 mIU / mL and <5 oocytes; c2 = 7.797 (df = 1, p = <0.047). The lowest chance was in 38-40 years (OR = 0.338, 95% CI: 0.147- 0.776, p = <0.011) with a longer lapse of infertility; 10-12 years (OR = 0.394, 95% CI: 0.181-0.858, p = 0.019). CONCLUSION: Our data suggest that in the >12 oocytes may be the optimal number to obtain, independent of the age. On the other hand the best chance to have a live birth is with an age <37, FSH <4.2 mIU/ mL and <5 oocytes. Fewer oocytes than previously deemed optimal, because the probability of having a euploid embryo in this group of people is much bigger.